An investigation into chemical and biological assays of new compounds from aloes - Mapp, R K (Rhodes University, Faculty of Pharmacy, Pharmacy, 1969)
The drug aloes has been known since earliest times and is mentioned in the Ebers papyrus of circa 1,500 B.C. Alexander the Great is reported to have sent a commission to Socotra to investigate the aloes grown there. The chemical composition of aloes is complex, and being of plant origin, subject to variation. Both the complexity of the chemical constituents and their biological variation has resulted in a very large volume of conflicting material being published on this drug export. Since aloes is used as a purgative for both human and veterinary use, it is obviously important that the dosage and consequently the active constituents, should comply to an accurate means of standardisation. To date, despite extensive world wide research into this drug such standardisation has not been achieved. Even the methods used for the assay of the principal constituent, aloin, vary considerably in their results, and to complicate matters new chemical principles have been isolated from aloes in recent years. Consequently the purpose of this work has been to investigate the main chemical assay methods currently in use, and to determine which was the most accurate, and why discrepancies occurred in the selected assay methods. furthermore the results obtained by chemical assay have been compared with those obtained by biological assay in an attempt to correlate aloin content with purgative activity. Newly isolated compounds have been investigated biologically for the first time, and the biological assays of the resinous, glycosidal and other compounds of aloes have been performed. Intro. p.1-2.
Keywords: Medicinal plants -- Research -- South Africa; Botanical chemistry; Aloe -- Analysis; Aloe -- Research -- South Africa; Aloe; Aloin